NUMERICAL CALCULATION OF EXTINCTION COEFFICIENT FOR DISLOCATION LOOPS WITH A CERTAIN ORIENTATION - I. P. Yaremiy; U. O. Tomyn; S. I. Yaremiy; M. M. Lukanyuk; H. M. Hodovska; Yu. I. Katrych (Vasyl Stefanyk Precarpathian National University, 2016)
Approximation formulas for the calculation of extinction coefficients in a wide range of radii and concentrations of dislocation loops oriented in certain directions were obtained. It was shown that received expressions make it possible to quickly calculate with satisfactory accuracy the angular dependence of extinction coefficient and speed up the calculation of theoretical rocking curves.